Management of Children with Psoriasis During the COVID-19 Pandemic - Nikolay N. Murashkin; Alexander I. Materikin; Eduard T. Ambarchian; Roman V. Epishev; Leonid A. Opryatin; Roman A. Ivanov (Вопросы современной педиатрии, 2021)
The spread of new coronavirus infection (COVID-19) changes specialists' approaches to patients with chronic diseases, including those with chronic dermatoses. The high risk of COVID-19 complications in patients with psoriasis is connected to the features of disease pathogenesis (such as high activity of proinflammatory cytokines) and used immunosuppressive therapy. Psoriasis affects up to 1% of children in Europe, while 10-20% of them have moderate or severe form of disease. These children may require immunosuppressive treatment, including genetically engineered biological therapy. There is only limited data on adults and children with psoriasis during the COVID-19 pandemic.